Hydrothermal synthesis and characterization of zeolite from Malaysia’s natural kaolin for adsorption of sodium ion (NA+) from seawater - Sazali, Norsuhailizah (2020)
Zeolite-A is widely known as aluminosilicate mineral that has been intensively used as an adsorbent in the adsorption process for desalination. Desalination is a technique to eliminate sodium ion and other minerals in the water. Because of the nature of seawater, which is very salty, the main purpose of the removal of sodium ion from seawater is to produce a source of clean drinking water. The capability of zeolite-A as an adsorbent makes it suitable to remove sodium ion from seawater. The raw kaolin from a different location (Perak and Johor) that acts as the main source of silica and alumina has been successfully studied to synthesized and transform into the ZeoliteA. The proposed synthesis of zeolite-A from kaolin has been reduced the cost of using synthetic reagent and high energy utilization. The various operating parameters to synthesis zeolite-A from both low-grade kaolin (Perak and Johor) were investigated to produce high crystallinity of zeolite. The alkaline solution (2-3 M NaOH) was added as a modification method for their conventional hydrothermal synthesis process. The calcination and crystallization process was recognized as an important processing stage for the synthesis. For the metakaolin process, the temperature 650 0C and time 240 minutes were used. The crystallization time of 12-16 hours with an aging treatment time of 24 hours was selected in the synthesizing of zeolite. The successful of synthesized Zeolite-A was further characterized by XRD, FESEM, FTIR, PSA and BET. The composition percentage of kaolinite from Perak kaolin (84 %) is higher compared to the Johor kaolin (40.6 %). As demonstrated in this work, Perak kaolin was successfully synthesized into Zeolite-A which give higher crystallinity percentage, 72.97 % compared to Johor kaolin, 46.72 % under 24 hours aging, with 2M NaOH and 12 hour crystallization time. The higher percentage of kaolinite from Perak kaolin gives higher crystallinity percentage of synthesizing zeolite-A compared to Johor kaolin. In addition, the BET surface area of Zeolite-A is higher, 5.26 m2 /g compared to natural zeolite, 2.9 m2 /g. The performance of adsorption capacity of sodium ion (Na+ ) toward synthesized Zeolite-A was further analyzed by batch adsorption analysis (Isotherm and Kinetic Model) and column adsorption analysis (Breakthrough curve model). The various parameter was applied to the batch experiment (Zeolite-A dosage, time, initial sodium ion concentration and volume) and column experiment (Zeolite-A dosage, initial sodium ion concentration and flow rate). For batch adsorption analysis, both the Langmuir model and Freundlich model were used to analyze the adsorption of sodium ion toward Zeolite-A. Langmuir isotherm model shows slightly better fitted with the correlation coefficient, R2 = 0.9074 compared to Freundlich isotherm, R 2= 0.9028. The result from the kinetic model shows the intra particle diffusion model gives better fitted with R2 value is 0.9117 compared to pseudo first order (R2= 0.732) and pseudo second order (R2= 0.8276). In addition, the calculated value of adsorption capacity at equilibrium, qe, is 88.4 mg/g by intra particle diffusion model gives the closest to the experimental value of qe, (92 mg/g) compared to pseudo first order (qe= 205.36 mg/g) and pseudo second order (qe= 104.1 mg/g). For column adsorption analysis, breakthrough capacity, qB was increased by increasing the bed height of zeolite-A and initial sodium ion concentration but decrease when increasing the flow rate. The column kinetic model shows the Adam Bohart model slightly better fitted with R2 range is 0.86-0.95 for flow rate, R2 = 0.82- 0.93 for bed height and R2 = 0.90-0.95 for initial sodium ion concentration compared to Thomas model, R2 = 0.84-0.94 for flow rate, R2 = 0.72-0.89 for bed height and R2= 0.78-0.88 for initial sodium ion concentration and Yoon and Nelson model, R2 = 0.84- 0.94 for flow rate, R2 = 0.69-0.89 for bed height and R2 = 0.78-0.87 for initial sodium ion concentration. It can be concluded that the performance of synthesizing zeolite-A from Perak kaolin was capable of adsorbing sodium ion from seawater solution.